Analysis of the presence of prtR proteinase gene in natural isolates of Lactobacillus rhamnosus - Pastar, I; Fira, D; Strahinić, I; Krstić, K; Begović, J; Topisirović, L; Jovanović, G (Folia microbiologica, 2006)
The region of the prtR gene coding for the active site of PrtR proteinase was detected in natural isolates of lactobacilli, previously determined as Lactobacillus rhamnosus. This region was present in all L. rhamnosus strains with proteolytic activity. The PCR primers used were constructed on the basis of the sequence of the catalytic domain of the prtR proteinase gene. These primers generated in colony-PCR procedure specific 611 1-bp product with DNA from natural isolates of L. rhamnosus. No PCR amplifications using these primers were obtained for closely related bacteria of genus Lactobacillus, regardless of their proteolytic activity. In addition, these primers could be used singly or in multiplex PCR together with the Lactobacillus genus-specific primers. Compared with the other proteinases within the genus Lactobacillus (PrtP, PrtB and PrtH) which retained the activity in cell-free proteinase extracts, PrtR proteinase showed proteolytic activity only under in vivo conditions (whole cells of the producing strains).
Keywords: Polymerase Chain Reaction; polymerázová řetězová reakce; Lacticaseibacillus rhamnosus; cysteinové endopeptidasy; DNA primery; bakteriální proteiny; Humans; DNA bakterií; DNA, Bacterial; Female; DNA Primers; Food Microbiology; Cysteine Endopeptidases; Bacterial Proteins; vazebná místa; ženské pohlaví; Catalytic Domain; katalytická doména; vagina; potravinářská mikrobiologie; Vagina; Binding Sites; lidé